Mepolizumab for chronic rhinosinusitis with nasal polyps (SYNAPSE): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10 (October 2021) - Han, Joseph K; Bachert, Claus; Fokkens, Wytske; Desrosiers, Martin; Wagenmann, Martin; Lee, Stella E; Smith, Steven G; Martin, Neil; Mayer, Bhabita; Yancey, Steven W; Sousa, Ana R; Chan, Robert; et al.
Summary: Background: Chronic rhinosinusitis with nasal polyps affects approximately 2–4% of the general population, and long-term use of systemic corticosteroids is associated with adverse effects. The aim of this study was to assess the efficacy and safety of mepolizumab in adults with recurrent, refractory severe bilateral chronic rhinosinusitis with nasal polyps. Methods: SYNAPSE was a randomised, double-blind, placebo-controlled, parallel-group, phase 3 trial done at 93 centres, mainly hospitals, in 11 countries. Eligible patients were aged 18 years or older with recurrent, refractory, severe, bilateral nasal polyp symptoms (nasal obstruction symptom visual analogue scale [VAS] score of >5), were eligible for repeat nasal surgery (overall symptoms VAS score >7 and endoscopic nasal polyps score of ≥5, with a minimum score of 2 in each nasal cavity) despite standard of care treatment, and had to have at least one nasal surgery in the past 10 years. Patients were randomly assigned (1:1), using permuted block design, to receive either 100 mg mepolizumab subcutaneously or placebo once every 4 weeks, in addition to standard of care (mometasone furoate intranasal spray for at least 8 weeks before screening and during the study, saline nasal irrigations, systemic corticosteroids or antibiotics, or both), as required, for 52 weeks. Site staff, the central study team, and patients were masked to study treatment and absolute blood eosinophil counts. The coprimary endpoints were change from baseline in total endoscopic nasal polyp score at week 52 and in mean nasal obstruction VAS score during weeks 49–52, assessed in the intention-to-treat population (ITT). This study is registered with ClinicalTrials.gov, NCT03085797 . Findings: From May 25, 2017, to Dec 12, 2018, 854 patients were screened for eligibility. 414 patients were randomly assigned with 407 included in the ITT population; 206 received mepolizumab and 201 received placebo. Total endoscopic nasal polyp score significantly improved at week 52 from baseline with mepolizumab versus placebo (adjusted difference in medians −0·73, 95% CI −1·11 to −0·34; p<0·0001) and nasal obstruction VAS score during weeks 49–52 also significantly improved (−3·14, −4·09 to −2·18; p<0·0001). Adverse events considered related to study treatment were reported in 30 (15%) of 206 patients receiving mepolizumab and 19 (9%) of 201 receiving placebo. On-treatment serious adverse events occurred in 12 (6%) patients receiving mepolizumab and 13 (6%) receiving placebo; none were considered related to treatment in those receiving mepolizumab. One death was reported in the placebo group (myocardial infarction; death occurred 99 days after the last dose) and was considered unrelated to the treatment. Interpretation: Mepolizumab treatment improved nasal polyp size and nasal obstruction compared with placebo, with no new safety indications, in patients with recurrent, refractory severe chronic rhinosinusitis with nasal polyps. These findings suggest that mepolizumab provides an effective add-on treatment option to standard of care in this population. Funding: GlaxoSmithKline.